Use of Water Quality Index and Pesticides‐Related Human Health Risk Assessment for Evaluating the Surface Water Sustainability Status of the Kakia‐Esamburmbur Agricultural Watershed, Narok County, Kenya - Wendyam Arsene Flavien Damiba; John Mwangi Gathenya; James Messo Raude; Patrick Gathogo Home (GeoHealth)
Abstract The increase in water contaminants threatens ecosystems and human health, underscoring the need for effective water quality (WQ) control. This study assessed the Kakia‐Esamburmbur catchment's water sustainability status for drinking purposes by analyzing water samples from the catchment. In‐depth physical, chemical, and microbiological investigations were undertaken using a dual approach. This entailed using the Water Quality Index (WQI) for domestic uses and applying a health risk assessment model. The study revealed that turbidity, total viable bacteria, fecal coliforms, and Escherichia coli exceeded WHO, East African, and Kenyan standards (EAS and KEBS) for domestic use and that 50% of samples tested for electrical conductivity also exceeded these guidelines. According to EAS for natural drinking water, 30% of water sources were classified as poor, 20% as very poor, and 50% as unsuitable for domestic use. Overall mean WQI values, based on standards, indicated that the WQ was unfit for domestic use. Nine pesticides associated with antibiotic resistance genes (ARGs) were identified and quantified using Pesticide Human Health Risk Assessment (PHHRA). As a result, 70% of water samples had high levels of carbendazim (CBD), rendering them unsafe for children and infants to consume. This was indicated by a hazard quotient (HQ) > 1 and hazard index (HI) > 1. Statistical evaluations showed geogenic and anthropogenic pressures control hydrogeochemical and microbiological processes in water.